LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK DISKUSI UNTUK SISWA KECANDUAN GAME ONLINE DI SMA AL AMANAH CIWIDEY - Muhamad Zamaludin; Ika Mustika; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to obtain an overview of group guidance using discussion techniques forstudents who are indicated to be addicted to online games at SMA AL Amanah Ciwidey, toobtainresultsfromtheimplementationofgroupguidanceservicesusingdiscussiontechniques for students who are addicted to online games at SMA AL Amanah Ciwidey,Student responses after being given groupguidance services using discussion techniquesfor students who are addicted to online games at SMA AL Amanah Ciwidey and theconstraintsofBKteacherswhenprovidinggroupguidanceservicesusingdiscussiontechniques for students who are addicted to online games at SMA AL Amanah Ciwidey.Thisresearchisadescriptivestudywithaqualitativeapproachwhereobservations,interviewsanddocumentationareusedfordatacollection.Keywords: GroupGuidance,DiscussionTechniques,OnlineGameAddiction